Faith and place an essay in embodied religious epistemology - Wynn, Mark, 1963- (Oxford : Oxford University Press, 2009)
'Faith and Place' considers how places come to acquire special religious significance, as sites for prayer or other kinds of devotional activity. It examines the ways in which sacred sites function, and the ways in which sites which have no explicitly religious import may come to bear a religious meaning.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sacred space; Knowledge, Theory of (Religion); Faith